2018
DOI: 10.1016/j.mce.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally-induced maternal hypothyroidism alters enzyme activities and the sensorimotor cortex of the offspring rats

Abstract: In this study, we used an experimental model of congenital hypothyroidism to show that deficient thyroid hormones (TH) disrupt different neurochemical, morphological and functional aspects in the cerebral cortex of 15-day-old offspring. Our results showing decreased glutamine synthetase (GS) activity and Ca overload in the cerebral cortex of hypothyroid pups suggest misregulated glutamate metabolism associated with developmentally induced TH deficiency. The C-MeAIB accumulation indicates upregulated System A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Meanwhile, previous researches suggested that untreated pregnant women with hypothyroidism may develop hypothyroidism and diabetes in the years after pregnancy [24,25]. Considerable research efforts have been devoted to untreated experimentallyinduced maternal hypothyroidism that might have serious consequences for offspring development like behavior, skin, brain [26][27][28]. However, few systematic studies have concerned the interaction between hypothyroidism and gestation.…”
mentioning
confidence: 99%
“…Meanwhile, previous researches suggested that untreated pregnant women with hypothyroidism may develop hypothyroidism and diabetes in the years after pregnancy [24,25]. Considerable research efforts have been devoted to untreated experimentallyinduced maternal hypothyroidism that might have serious consequences for offspring development like behavior, skin, brain [26][27][28]. However, few systematic studies have concerned the interaction between hypothyroidism and gestation.…”
mentioning
confidence: 99%
“…TH deficiency causes wide range abnormalities in the offspring including defective in the neuronal migration, reduced myelination, growth of axons, and dendrites which are associated with motor, visual, and auditory functions [ 20 ]. Hypothyroidism also associated with other histomorphological changes within the cerebellum, involving fostered neuronal death with the internal granular layer, fostered perdurance of the external granular layer, defects within granular cell migration, impaired Purkinje cell dendritogenesis, delayed myelination, and increased cell apoptosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent results demonstrated that CH induces reactive oxygen species production, which is affiliated with LPO and GSH depletion, these results suggest that hypothyroidism causes redox imbalance and oxidative stress in the cerebral cortex of immature rats. It has been reported that increased oxidative stress in granulosa cell and oocyte necroptosis due to RIPK signaling pathways [ 20 ]. In a study RIPK3 has been associated with microvascular ischemia-reperfusion injury through increased xanthine oxidase-dependent oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that even normal levels of T3 in the CSF, astrocyte-TH dysregulation in the brain due to genetic modification contribute to dementia in the elderly. Energy metabolism in hypothyroid brain leads to disruption in astrocyte cytoskeleton as well as glutamatergic and cholinergic neurotransmission, Ca 2+ equilibrium, redox balance, morphological and functional aspects in the cerebral cortex even in young rats from maternal hypothyroidism [147].…”
Section: Thyroid Regulation Of Brain Metabolic Ratementioning
confidence: 99%